POLA ASUH ORANG TUA: PERSPEKTIF KONSELING DAN ALQURAN - Thalib, M. (Hunafa: Jurnal Studia Islamika, 2007)
In Â psychological point of view whatever occurs in an adult is influenced by his or her life condition in his or her adulthood, particularly in the first years of his or her age. Offspring and milieu give a major influence to the formation ofÂ  attitude and of behavior of a child. Rearing model constitutes a concept for educating a child in order that he or she obtains his or her meaningful life. For this target and meaningful life, an individual is demanded to grasp however the life is he or she must assume it a positive reality. It is within this context that rearing model of parents is highly needed for a childâs psychological development.Kata Kunci: Â pola asuh orang tua, konsep konseling, konsep AlquranÂ